A arte do improviso na poética de Geraldo Alves: o sertão ao som da viola - Costa, Maria José Ferreira da (2009)
That research intended to discuss the transformations that art of the surprise, the singing, is passing in elapsing of the time in his displacement between the field and city. In view of that, I propose the recognition of the singing as a cultural expression of resistance. In that direction, he became vital to reconstitute Geraldo Alves' memory and of people that he interacts with yours to create poetic. This way, the oral sources made possible the identification of many languages that they interlaced the existences, the preservation processes, the strategies of sociability and the changes of that manifestation Northeastern cultural imbricate of memories brought that they in the spaces field / city. The theme of that research was defined, mainly, for the conception of the culture popular view in her dynamicity, that allowed to be considered the interviews of the abrupt and listeners as the central source of that research. For so much, I used the interviews as impregnated texts of meanings, trying to build a history capable to think the present as a dimension of the social transformation of those that were the margin of the official historiography, daily subjects that they live and they make her own one recounts. Besides the oral reports, I chose as source, pamphlets of popularization of singings as well as the book "Entranhas da Terra by Geraldo Alves. Verses were done of surprise and the register of the informal conversations in the intervals of the singings. My objective when I interviewed those social agents went to know their life paths, looking for to understand the perception that they bring of singings and their involvements with that art, in the attempt of understanding as their memories of the past are rebuilt in the present. The theoretical presuppositions of that research are anchored in the Popular Culture, in the Social History and in the presuppositions of the Oral History. Authors as Hall, Benjamin, Portelli, Canclini, among other, were fundamental for this work. I could notice in the research that when changing their experiences, the singers and the public they are going weaving a net, in the webs of the narrative singing, gathering do and pleasures in rememorization exercises. At the same time in that the body enters in action, the mind works memories "planted in those fertile soils", of seeds and future memories, guaranteeing the possibility to the reproduction of the memory. Verification, in that research, was that the singing in the urban spaces, like São Paulo, is a resistance practice that became the thread that weaves the singers' identity and his/her public, expressing values, habits, memories, dreams and desires of the Northeasterners that had to leave the field with the dream of a better life in the city